Extended Intergroup Contact and Outgroup Attitude of Students in Public and Religious Homogeneous Schools: Understanding the Mediating Role of Ingroup Norms, Outgroup Norms, and Intergroup Anxiety - Yustisia, Whinda; Hudiyana, Joevarian; Muluk, Hamdi (Jurnal Psikologi, 2021)
Previous studies had shown the benefits of extended intergroup contact for outgroup attitude, mainly when direct intergroup contact is blocked. However, there have not studies that attempt to directly compare the role of extended contact in outgroup attitude across different contexts. The present study aimed to fill the gap by examining the relationship of extended intergroup contact and outgroup attitude in three different contexts: public schools, moderate Islamic Boarding School, and fundamentalist Islamic Boarding School. These schools differ in the level of group heterogeneity. Possible mechanisms that could explain the relationship were also examined: ingroup norms, outgroup norms, and intergroup anxiety. Two correlational studies were conducted to test the hypotheses—study 1 employed 126 Muslim public high school students employed as participants, study 2 employed 112 participants from a more fundamentalist Islamic Boarding School and 230 participants from a more moderate Islamic Boarding Schools. Across studies, we found evidence that extended intergroup contact indirectly predicted outgroup attitude. However, different social contexts involve different mechanisms. This difference is attributed to direct intergroup contact.